(3CWHGb GdPgHs - (3GdCUagGfj , YHO GdeDef Hf gHI Gddg, TQa GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG CSHdJ ef LdGjH cQec hSFdJ ef fYeJc hTcQc Ydi eG ChQOJ s
(3BNQgG (B:s
(3JeJ GdYQhV GdefShHI Edi GHf GdMGLH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdcJGH YHGQI Yf MGTjI Ydi cJGH ebGeGJ GdMQjQi jdjg cJGH HGdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B170s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdCOHs